The Influence Of Leadership Style And Organizational Culture On Performance With Job Satisfaction As An Intervening Variable - Temu, Tobias Joni; Triyonowati, Triyonowati; Djawoto, Djawoto (UNIVERSITAS PAKUAN, 2023)
This study aims to determine and analyze the influence of transformational leadership styles and organizational culture on employee performance through job satisfaction. The type of research used is quantitative descriptive research. The type of data in this study is subject data in the form of respondents' characteristics in the form of gender, age, education, length of work, and work experience obtained directly from KSP Kopdit Tuke Jung Maumere employees. The sampling technique used in this study is probability sampling. The sample of this study was all KSP Kopdit Tuke Jung Maumere employees, totaling 51 people. Data analysis is processed using Path Analysis. The results of the analysis show that transformational leadership style affects job satisfaction, organizational culture does not affect job satisfaction, transformational leadership style, and organizational culture directly affect employee performance, and job satisfaction does not mediate leadership style and organizational culture on employee performance.